A contribution to the study of Rodolphe Archibald Reiss's activities in the Kingdom of Serbs, Croats, and Slovenes (1919-1929) - Milošević Srđan (NBP: Nauka, bezbednost, policija, 2021)
In this paper two hitherto unknown letters related to the activity of Dr Archibald Reiss in the Kingdom of Serbs, Croats, and Slovenes (1919-1929) are presented and commented on. While Reiss's activities during WWI (1914-1918) are well documented and thoroughly researched, the knowledge about his engagement in the first post-war decade remains fairly scarce, due to the lack of sources. However, the available sources generally confirm that there was insurmountable tension in the relations between R. A. Reiss and the authorities of the Kingdom of Serbs, Croats, and Slovenes, almost from the very beginning of his "second term" in the service of the Belgrade government. The two Reiss's letters addressed to the Regent and King Aleksandar, published in this paper (one of which was hitherto unknown), clearly reveal the peculiar relationship between them. Another letter, rather a short diplomatic report, sheds some new light on the conditions of Reiss's return to the service of the government in Belgrade in 1919. The research clearly shows that Reiss occupied the position of the head of the Technical Service at the Department for Public Safety and also points out at his official reporting missions to Macedonia, on the request of the Minister of the Interior, in 1921 and 1922.